Systematics and evolution of the Meriones shawii/grandis complex (Rodentia, Gerbillinae) during the Late Quaternary in northwestern Africa: Exploring the role of environmental and anthropogenic changes. (15th May 2017) - Stoetzel, Emmanuelle; Cornette, Raphaël; Lalis, Aude; Nicolas, Violaine; Cucchi, Thomas; Denys, Christiane
Abstract: Rodents of the Meriones shawii/grandis complex have been attested to in North Africa since the Middle Pleistocene and are abundant in archaeological sites. Today, they are widely spread and represent a major pest to local human populations. This complex, therefore, represents an accurate model for investigating the roles of climate change and human impact in shaping Quaternary faunal diversity and distribution. Many gray areas still exist regarding the systematics, ecology and geographical distribution of this complex, for both present and past populations. The purpose of this study is to compare modern genotyped and fossil Meriones specimens in order to 1) clarify the current systematics and distribution of the Meriones populations of the shawii/grandis complex, 2) document the taxonomic diversity in fossil Meriones from northwestern Africa, and 3) track their phenotypic and biogeographic evolution through time. To answer these questions we used geometric morphometrics on skulls (landmarks) and first upper molars (landmarks and sliding landmarks). We evidenced the existence of two morpho-groups within the M. shawii/grandis complex, with a clear geographic pattern ( M. grandis in Morocco vs. M. shawii in Algeria and Tunisia). Currently only one morpho-group, attributed to M. grandis, seems to exist in Morocco, with a small overlap with M. shawii in the most eastern part of the country. However, according to fossil data, M. shawii was also present in Atlantic Morocco during the Late Pleistocene. We have also highlighted the impact of Holocene climate change and habitat anthropization on this arid adapted group. During the Middle Holocene, a major climatic event (last interglacial optimum) seems to have induced a demographic collapse in Moroccan populations and the disappearance of the shawii clade from Morocco (except in the most eastern areas). Both species then re-expanded, benefitting from the increasing aridity and the new ecological niche driven by agriculture dispersal from the Neolithic onwards. Highlights: A combination of genetic and morphometric data was used. Taxonomic difficulties with the M. shawii/grandis were solved. Morphogeometric data allowed precise species identification of fossil specimens. Demographic and biogeographic history during the Quaternary was reconstructed.